Oscarella balibaloi, a new sponge species (Homoscleromorpha: Plakinidae) from the Western Mediterranean Sea: cytological description, reproductive cycle and ecology - Pérez, T.; Ivanišević, J.; Dubois, M.; Pedel, L.; Thomas, O.P.; Tokina, D.; Ereskovsky, A.V. (Marine Ecology, 2011)
A new homoscleromorph sponge species was observed for the first time in 2002 along the coast of Provence (France) and since then, several investigations have been implemented. The new homoscleromorph species is devoid of skeleton and it is thus related to the Oscarella genus. Oscarella balibaloi sp. nov. has been found in several littoral submarine caves of the Western Mediterranean Sea (France and Spain). After several years of monitoring, we show that this sponge is becoming abundant in several locations. The species has a peculiar habit, often overgrowing massive sponges, gorgonians or some erected bryozoans. Oscarella balibaloi sp. nov. is thinly encrusting, with an irregular morphology, lobate surface, and soft and very slimy consistency. Its color is white to orange. At the cytological level, this new species is characterized by three distinct types of cells with inclusions in its mesohyl: one with vacuoles and the others with paracrystalline inclusions. The reproduction pattern is very similar to other Oscarella species. We also present a specific metabolic fingerprint and compare it to that of other Mediterranean Oscarella species.